(untitled) (De Musica, 2014)
Concrete and abstract. Aesthetic formalism from Johann Friedrich Herbart to Robert Zimmermann. Zimmermann (1824–1898) contributes an important Ästhetik to the history of aesthetic formalism and he is a major representative of Herbartianism in Vienna. In my analysis I show, on the one hand, that he aims to delivering a systematic work, based on the insights which Herbart (1776–1841) had already provided, without treating them exhaustively. On the other hand, I argue that it is not unproblematic to reconcile Zimmermann’s views with Herbart’s ideas, especially when crucial notions such as ‘form’ and ‘relationship’ are considered. Paradoxically, the distance between the two thinkers ultimately emerges from the essay in which Zimmermann examines the analogy Herbart himself had drawn between music theory and practical philosophy. After analysing Zimmermann and Hostinský’s debate concerning Herbart’s axiological formalism, I conclude that, whenever Zimmermann broadens Herbart’s theories, pursuing their explanation and systematic completion, he betrays the main issues of Herbartian formalism and philosophy; Herbart’s most profitable theories―concrete formalism and functionalism―are thus abandoned in favour of abstract, void constructions.